Torrefaction of rice husk as preparation of coal-biomass co-firing and its propensity on ash deposition (Rudarsko-geološko-naftni zbornik, 2024)
The most extensive use of coal in Indonesia is for electricity generation. Due to increasing concerns about climate change and the need to reduce emissions caused by burning coal, biomass-based fuels are becoming more competitive. The biomass carbonization process, or torrefaction, to produce solid fuel has been introduced elsewhere. This research uses sub-bituminous coal and rice husks, considering Indonesia's large potential for both. The primary objective of this research was to determine the optimal temperature and residence time for the rice husk torrefaction process, intending to reduce the alkali oxide content that led to ash deposition. This was necessary due to the limited information available, particularly for local rice husks from Indonesia. We carried out the rice husk torrefaction at 300, 350, and 400°C temperatures for 30, 60, and 90 minutes. The results show that a temperature of 350°C and a residence time of 60 minutes were the optimal conditions. In these conditions, the potassium and sodium oxides decreased, and the calorific value increased. To get a coal-rice husk blending with a calorific value greater than 5,000 cal/g (ADB), the proportion of coal to rice husk should be 90 and 10%, respectively. The rice husk torrefaction process did not have much influence on the occurrence of ash deposition. However, the torrefaction process increased the calorific value, reduced transportation costs due to the lower moisture content, and improved grindability so that it was easy to blend with coal.